Robin Hood or Matthew? Children's Reasoning About Redistributive Justice in the Context of Economic Inequalities. Issue 4 (28th January 2021) - Essler, Samuel; Paulus, Markus
Abstract : How should one respond to ubiquitous economic inequalities? The legend Robin Hood suggests to take away from the wealthy to benefit the poor, whereas another strategy holds the opposite (Matthew effect). Here, 3‐ to 8‐year‐old children ( N  = 140) witnessed protagonists performing redistributions (e.g., Robin Hood, Matthew) of necessary and luxury resources between a wealthy and a poor child. Results showed that, with age, children increasingly approved of Robin Hood and increasingly disapproved of Matthew. In addition, reasoning about others' welfare mediated the effect of age on children's evaluation of Robin Hood, but only for necessary resources. This suggests that children regard restorative justice actions as a strategy to address social inequalities when it increases the welfare of disadvantaged agents.